(untitled) (Experimental biology, 2016)
The objects of study were the cultures of bacteria and yeast isolated in the coastal zone of the Caspian Sea, adjacent to the oil fields on the peninsula Buzachi. 8 dominant cultures of microorganisms, demonstrating strong growth in medium containing crude oil, from local field, diesel and gasoline were isolated from water samples taken from peninsula Buzachi region of the Caspian Sea. Identification of these cultures according standard morphological, physiological and biochemical characteristics showed that they belong to the bacteria genera Pseudomonas, Bacillus, Rhodococcus, Ochrobactrum, Klebsiella, Lysinibacillus, Erwinia and the yeast genus Yarrowia.